A Survey of late night TV viewing among Metro Manila residents - Reyes, Ma. Regina E.
The decision to undertake this descriptive study was borne out of a sincere desire to find out what viewers need and want from this most powerful of all media, television. The researcher used the survey method to find out who among televiewers in Metro Manila watch late night programs, most of which are news and public affairs programs. The respondents included residents in selected five urban areas in the metropolis. The initial findings may not be very surprising to those who are already in media and have a knowledge of their market. In determining th profile of late night television viewers, the study showed that a majority of the respondents who said they watched late night TV belonged to the low income bracket, earning a monthly income of 20,000 pesos and below. The study's demographic findings provided an image the typical Metro Manila late night televiewer. It was also revealed that the respondents had a high level of exposure to late night television programs. This was supported by the moderately high frequency of watching these shows. A big number of the respondents also showed a marked preference for the two leading TV networks, ABS-CBN 2 and GMA 7 in their late night television viewing. On the other hand, it was also found out that the respondents did not have a high level of knowledge on late night news and public affairs programs. This was determined after conducting a 17-item knowledge test on the respondents and assessing their scores by way of the Likert scale. The test showed that very few got an "Excellent" rating, while the majority got between "Good" and "Fair" ratings. Based on the responses it obtained, the study acknowledged several factors that affect the viewers' preferences for late night TV programs - choice of topics, format, hosts, visual elements. However, it also recognized the need to further explore programming possibilities and probe deeper into the needs and wants of the television audience.